THE EFFECTIVENESS OF ULTRASOUND IN THE PRE-GRAVID PREPARATION OF PATIENTS WITH INFLAMMATORY DISEASES OF THE FEMALE GENITAL ORGANS - Annamuratova Muhayyo Saporboyevna; Ozodova Nargiza Muminjonovna (Scholar Express Journals, 2021)
The article provides recommendations for the pre-gravid preparation of patients with inflammatory diseases of the female genital organs and their consequences in infertility and miscarriage. The indications, examination methods in order to clarify the genesis of the inflammatory disease and the principles of therapy are set out on the basis of clinical recommendations of 2012. The effectiveness of a broad-spectrum antibacterial drug amoxicillin / clavulanate in the program of preparing for pregnancy in patients with inflammatory diseases of the pelvic organs is noted, given the significant increase in the incidence of bacterial infection. flora.
Keywords: Ultrasound diagnostics; pre-gravid preparation; urinary tract infection